2021
DOI: 10.3390/agronomy11101986
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Night Low Temperature on Agronomical Traits of Thirty-Nine Pepper Accessions (Capsicum annuum L.)

Abstract: Pepper plants are subject to complex environmental factors including abiotic and biotic stresses in fields, as well as the significant effects of climate changes, including low and high temperatures. Low temperature stress in the growth and development of pepper plants is one of the most critical issues, and directly impacts the crop yield and productivity of pepper plants. Therefore, it is essential to select and breed low temperature-(LT) tolerant pepper (Capsicum annuum L.) cultivars. This research was cond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
(59 reference statements)
3
5
0
Order By: Relevance
“…In the agreement with our previous studies of pepper genotypes under LT condition [24], our current finding also showed that the NFL among pepper accessions showed no remarkable difference between the LCD and NT.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the agreement with our previous studies of pepper genotypes under LT condition [24], our current finding also showed that the NFL among pepper accessions showed no remarkable difference between the LCD and NT.…”
Section: Discussionsupporting
confidence: 93%
“…Effect of LCD within 25% in seedling stage on the subsequent growth stages of agronomical traits showed that it might be critical for recovery of pepper plants and significantly affect the development of some vegetative and reproductive parameters. It is well known that, LT significantly reduces the growth rate of plants [2,8,23,24,29], which was detected in plants with LCD in the present study, where lag behind in growth rate of PH in the percentage ratio than NT plants within 50 DAT was determined. Furthermore, a decrease of value of the differences in development was observed but the ranges depended on accession.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations